Implementation of Audiolingual Method in Increasing Students' Learning Motivation at Nurul Mun'im Islamic Elementary School - Hasanah, Lailatul Firdaus; Fawaid, Achmad (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2023)
The background of this research is motivated by the declining interest of students at MI Nurul Mun'im in learning Arabic. The reason is the lack of interesting learning methods, so there is no motivation for students to follow learning with enthusiasm. Efforts that must be made include the selection of suitable and interesting methods to use that can make learning easier to understand and not cause boredom when teaching and learning activities take place in the classroom. Therefore, researchers chose the audiolingual method as a method of learning Arabic in this study. The audiolingual method means listening and then speaking so that students not only focus on one understanding but are also expected to be able to repeat what they heard before with no errors. The research method used this time is a method with a qualitative approach of the case study type, which is in accordance with its characteristics, namely a method that is in social research. The data collection techniques include observation, interviews, and documentation. The research results are summarized as follows: Students' interest in learning is also greatly increased, as marked by the enthusiasm of students during class, the enthusiasm of students in participating in learning, and a sense of pleasure and love to learn Arabic. This is certainly inseparable from the role of the teacher who has chosen the audiolingual method as a method of learning Arabic. A good teacher and the selection of methods that are suitable for students will make students play an active role during learning activities.